Analisis semiotika ferdinand de saussure terhadap penggambaran benjamin netanyahu dalam karikatur hajjaj_cartoons - FAUZIL, MOH FATAHILLAH (Maliki Interdisciplinary Journal, 2025)
This study aims to analyse the portrayal of Benjamin Netanyahu in cartoons by Hajjaj_Cartoons using Ferdinand de Saussure's semiotic approach. Cartoons, as a form of visual art, play an important role in conveying social and political criticism, especially in the context of controversies involving public figures such as Netanyahu. Through semiotic analysis, this study identifies the visual signs used in the cartoons and relates them to the meanings they produce. The results of the analysis show that these caricatures not only serve as entertainment, but also as a medium for creating social and political awareness, as well as expressing criticism of policies that are considered unfair. Thus, this study contributes to the understanding of how caricature art can be used to highlight global issues and depict complex social realities.